A Histopathological Study of Granulomatous Inflammation - Permi, Harish S.; K., Jayaprakash Shetty; Padma, Shetty K.; S., Teerthanath; Mathias, Michelle; Y., Sunil Kumar; L., Kishan Prasad H.; Chandrika (Journal of Health and Allied Sciences NU, 2012)
Granulomatous inflammation is a distinctive pattern of chronic inflammation that is encountered in a limited number of infectious and non-infectious conditions. Recognisation of granulomatous pattern and finding the etiology in a biopsy specimen is very important for specific treatment and outcome of the disease. We aimed at finding the etiology of all granulomatous lesions on tissue biopsy sent for histopathogical examination. A study was done at K S Hegde Medical Academy of Nitte University, Mangalore from January 2009 to December 2010. All the cases which were diagnosed as granulomas on Hematoxylin and Eosin stained sections were selected. Special stains like Ziehl-Neelsen stain, Gomori's Methenamine silver, PAS, Fite Faraco were done whenever required. We encountered 275 granulomatous lesions in our study. The most common sites were skin and subcutaneous tissue, lymph nodes, bones and joints. The commonest cause of granulomas was tuberculosis, followed by leprosy, foreign body granulomas, fungal infections, rhinoscleroma, parasites, tumor granulomas and actinomycosis. The morphological features and special staining helped us to find the specific etiology of granulomas in 253 cases whereas it could not be determined in 22 cases even after special stains. Thus we conclude that histopathological examination of granulomatous lesions helped us to find the exact etiology of granulomas in 92 % of cases. The correlation of histopathology with polymerase chain reaction (PCR) serological tests and culture correlation would have helped to find the specific etiology in the remainder of cases.
Keywords: Granuloma; histopathology; special stains; etiology